2022
DOI: 10.1177/1358863x211068888
|View full text |Cite
|
Sign up to set email alerts
|

Total body recumbent stepping vs treadmill walking in supervised exercise therapy: A pilot study

Abstract: Background: Treadmill walking is the most commonly recommended exercise modality in supervised exercise therapy (SET) for peripheral artery disease (PAD); however, other modalities may be equally effective and more tolerable for patients. The primary aim of this single-blind, randomized pilot study was to compare the feasibility, safety, and preliminary efficacy of a treadmill walking (TM) versus a total body recumbent stepping (TBRS) exercise program for treatment of PAD. Methods: Participants ( n = 19) enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
(55 reference statements)
0
11
0
Order By: Relevance
“…23 Examples include arm cycling, [24][25][26] leg cycling, 25,26 and, most recently, total body recumbent stepping (TBRS). 27 Many of these studies have shown patient improvement following these alternative modes of exercise. In this issue, Salisbury and colleagues report the outcomes of a randomized pilot study comparing TBRS to traditional treadmill walking within a clinical supervised exercise program, demonstrating similar walking improvements in both groups.…”
Section: Gap #4: Identification Of Optimal Individual Therapies and M...mentioning
confidence: 99%
See 1 more Smart Citation
“…23 Examples include arm cycling, [24][25][26] leg cycling, 25,26 and, most recently, total body recumbent stepping (TBRS). 27 Many of these studies have shown patient improvement following these alternative modes of exercise. In this issue, Salisbury and colleagues report the outcomes of a randomized pilot study comparing TBRS to traditional treadmill walking within a clinical supervised exercise program, demonstrating similar walking improvements in both groups.…”
Section: Gap #4: Identification Of Optimal Individual Therapies and M...mentioning
confidence: 99%
“…In this issue, Salisbury and colleagues report the outcomes of a randomized pilot study comparing TBRS to traditional treadmill walking within a clinical supervised exercise program, demonstrating similar walking improvements in both groups. 27 However, it remains to be determined in whom nonwalking exercise is more effective compared to walking exercise. Thus, larger definitive trials testing alternative modes of exercise versus walking exercise are needed to determine best practices for different subgroups of patients with PAD.…”
Section: Gap #4: Identification Of Optimal Individual Therapies and M...mentioning
confidence: 99%
“…In this issue of Vascular Medicine , two original research investigations describe preliminary results of novel exercise interventions for PAD. 2,3 Identifying novel forms of exercise is important for patients with PAD who prefer an alternative to walking exercise or who are unable to participate in walking exercise due to extreme ischemic leg symptoms or frailty. Lanzi and colleagues report a pilot study of descending stair walking as an alternative form of exercise for people with PAD.…”
mentioning
confidence: 99%
“…Salisbury and colleagues studied the effects of 12 weeks of total body recumbent stepping, compared to traditional treadmill exercise training, in a pilot randomized clinical trial of 19 people with PAD. 3 Total recumbent stepping exercise is a low-impact aerobic exercise, consisting of pushing pedals (i.e. ‘stepping’) while in a reclined position.…”
mentioning
confidence: 99%
See 1 more Smart Citation